2008
DOI: 10.1634/stemcells.2008-0039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stromal-Derived Inducing Activity in the Generation of Dopaminergic Neurons from Human Embryonic Stem Cells

Abstract: STEM CELLS 2008;26:1517-1525 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 49 publications
2
74
0
Order By: Relevance
“…Spontaneous differentiation of hASC-iPS cells into cells of mesoderm and endoderm lineages was then detected with appropriate markers by immunofluorescence. Differentiation into dopaminergic neurons was carried out by co-culture of hASC-iPS cells with PA6 cells as previously described for hES cells (28).…”
Section: Quantitative-pcrmentioning
confidence: 99%
“…Spontaneous differentiation of hASC-iPS cells into cells of mesoderm and endoderm lineages was then detected with appropriate markers by immunofluorescence. Differentiation into dopaminergic neurons was carried out by co-culture of hASC-iPS cells with PA6 cells as previously described for hES cells (28).…”
Section: Quantitative-pcrmentioning
confidence: 99%
“…Other protocols for neural differentiation involved suspension cultures to generate embryoid bodies and culture in serum-free medium (Roy et al, 2006;Iacovitti et al, 2007). These protocols enable a significant 188 F. Wianny and J. Vezoli: Transplantation in the nonhuman primate MPTP model of Parkinson's disease enrichment of the population into neural progenitors that expressed NESTIN, SOX1, PSA-N-CAM (polysialylated neural cell adhesion molecule), PAX6 and SOX2 (Kawasaki et al, 2002;Ben-Hur et al, 2004;Perrier et al, 2004;Park et al, 2005;Sanchez-Pernaute et al, 2005;Takagi et al, 2005;Vazin et al, 2008;Doi et al, 2012). Midbrain DA specification of these neural precursors can then be induced by addition of FGF8, a mid-and hindbrain organizing morphogen, and SHH, a ventralizing morphogen (Perrier et al, 2004;Zeng et al, 2004;Park et al, 2005;Yan et al, 2005;Yang et al, 2008;Cooper et al, 2010;Doi et al, 2012), and/or by treatment with FGF2 and FGF20 -a secreted protein that enhances the survival of primary DA neurons (Ohmachi et al, 2000;Takagi et al, 2005;Morizane et al, 2013).…”
Section: Da Neurons Isolated From Primate Pscs or By Direct Reprogrammentioning
confidence: 99%
“…Discovered in 2000 for its ability to induce midbrain dopaminergic neurons from mESCs, stromal cell-derived inducing activity (SDIA) refers to the factors secreted from or imbedded in the cell membrane of PA6 cells or other bone marrow cells which have been shown to promote dopaminergic differentiation (Kawasaki et al, 2000). Studies on fixed PA6 cells and on mitomycin c treated and irradiated cells show a reduction in ability to differentiate to dopaminergic neurons (Vazin et al, 2008). Microarray studies examining the factors secreted from these cells have suggested 8 possible categories (IGF, FGF, Notch, www.intechopen.com Dopaminergic Neurons Derived from Human Embryonic Stem Cell Derived Neural Progenitors: Biological Relevance and Application 397 PDGF, SHH, TGFβ, VEGF, Wnt) for potential secreted factors (Swistowska et al, 2010).…”
Section: Dopaminergic Differentiationmentioning
confidence: 99%
“…Elucidating the factors expressed in and secreted by stromal cells used to differentiate dopaminergic neurons included microarray studies. One study found that the cell membrane of stromal cells expressed FGF7, hepatocyte growth factor and vascular endothelial growth factor, which were sufficient to induce dopaminergic differentiation (Vazin et al, 2008). A microarray examining the mRNA expression of PA6 cells found IGF2 and several IGF binding proteins, FGF10, DLK1 NGF, SHH, TGF3β, VEGF and Wnt RNAs to be highly expressed in PA6 cells (Swistowska et al, 2010).…”
Section: Dopaminergic Differentiationmentioning
confidence: 99%